Genetic diversity in the natural populations of Pinus kremfii in Tay Nguyen, Vietnam using ssr markers - Phong, Dinh Thi; Thu Hien, Vu Thi; Lieu, Tran Thi; Hiep, Nguyen Tien (Academia Journal of Biology, 2014)
In this study, 17 SSR markers were used to investigate genetic variation within and between four populations of P. krempfii in highland of Vietnam. There are 8/17 SSR markers revealed polymorphic. Among 42 putative genetic alleles were amplified, of which 32 were polymorphic (accounting for 76.19%). The genetic diversity were highest in Cong Troi population (h = 0.150, I = 0.415 and PPB = 52.95) and the lowest in Hon Giao population (h = 0.115, I = 0.330 and PPB = 47.06). The number of private alleles (Ap) was only found in three populations of Yang Ly (0.059), Cong Troi (0.118) and Chu Yang Sin (0.294). The level of low molecular changes between populations (11.94%) and high among individuals in the population (88.06%) was found. The genetic similarity among Pinus kremfii samples in Tay Nguyen ranged from 59% to 100%. The gene flow (Nm) over all P. kremfii populations per marker was relatively high, ranging from 1,813 to 10,796. Overall, we recommend a combination of conservation for P. krempfii.